Psychology of Human Relations - Scarbrough, Stevy (Open textbook library., 2023)
Understanding human relations is a valuable skill for anyone entering into the job market. The aim of this textbook is to aid readers in understanding their own behaviors and the behaviors of others with the intent of engaging in positive interactions in personal and professional spaces.